THE COOPERATION BETWEEN CONVENTIONAL COMMERCIAL BANKS AND RURAL BANKS FOR FINANCIAL INCLUSIVENESS IMPROVEMENT OF SMALL, MEDIUM AND MICRO ENTERPRISES - Usanti, Trisadini Prasastinah; Setiawati, Anindya Prastiwi (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
One of the accesses to funding for MSMEs is by inclusive financing which conducted through the collaboration between conventional commercial banks (BUK) and rural credit banks (BPR) with executing, channeling and joint financing schemes. The MSMEs Credit Banking Cooperation (KPKU) between BUK and BPR aims to be mutually beneficial with the ultimate goal is for more financed MSMEs by banks. For BPRs that have limited funds, the KPKU is the main alternative source of funds apart from savings and time deposits. The executing, channeling and co-financing schemes have different characters, especially to parties that dividing the funds to MSMEs debtors and parties who bear the risk due to non-payment funds that have been distributed to MSMEs. This research is a normative research using statutory and conceptual approach. This research concludes that there are three schemes have different characteristics, especially regarding to the parties that distributed the funds to MSME debtors and parties who guarantee the risk due to MSME debtors defaulting.